Inibição da adesão bacteriana por nanopartículas revestidas de vesículas bacterianas de membrana externa (OMV) - Gonçalves, Mariana Ottaiano (2023)
Antibiotic resistance is a global health threat. To combat resistant microorganisms, it is crucial to find natural alternatives with antimicrobial and anti-inflammatory properties. An innovative approach involves coating nanoparticles with biological membranes, transferring their properties and activating immune responses, potentially reducing multidrug-resistant infections. Bacterial outer membrane vesicles (OMVs) are spherical, non-replicating structures, naturally produced from the outer membrane of Gram-negative species, which allow the inheritance of natural characteristics of the bacteria, and which can compete with binding sites and thus inhibit bacterial adhesion on host cells. In this work, we synthesized therapeutic nanomaterials based on poly(lactic acid-co-glycolic acid) (PLGA) coated by OMVs in order to evaluate their in vitro interaction between pathogen and host, and their potential applications in nanomedicine. There were no significant differences in structure or physicochemical properties of OMVs isolated from K. pneumoniae under different bacterial culture conditions. In parallel, PLGA nanoparticles were synthesized using the nanoprecipitation technique with different fluorescent markers. The particles had a size ranging between 100 and 220 nm and a surface charge ranging between -30 and -35 mV. Then, the particles were coated with the vesicles extracted through sonication and the coated nanocarriers had a size of 200 nm and a yield of 1 x 1010 part/mL. Finally, these nanocarriers were tested for internalization in host and pathogenic cells and anti-adhesion capacity in lung cells. Our results predict the ability of nanocarriers to prevent bacterial adhesion in lung cells at certain times, concentrations and types of incubation. These results may help to understand how hybrid nanomaterials behave towards the host and the pathogen, and bring important benefits to the development of nanomedicine.